Sustainability—differently - Dymitrow, Mirek; Halfacree, Keith (Bulletin of Geography. Socio-economic Series, 2018)
It is increasingly appreciated how all societies contain many ‘wicked problems’ or socio-cultural challenges that are multidimensional, hard to pindown and consequently extremely challenging to solve. Obtaining functional and inclusive societal organisation is not a simple matter of ‘doing it’ by subscribing to winning formulae as there are, for example, many choices to be made in the process. Moreover, given that conceptual frameworks always guide thoughts, judgments and actions, how we relate to ‘sustainability’ specifically becomes relevant if we aim to achieve a more liveable society. This journal issue expressly engages with the consequent need to recognise this complexity. It assembles a set of ‘brave’ takes on far-advanced problems bedevilling conventionally conceptualised paths towards sustainability. Arguing against oversimplification that comes from domination of polarising concepts and unquestioned practices and rhetorics, the aim is to foster explorations into new territories from which we may learn. Ultimately, the desire to deconstruct pernicious divisions and create new hybrid syntheses can progress sustainability.